Ecological resilience in tropical Andean lakes: A paleolimnological perspective. Issue Volume 67:Issue S1(2022)Special issue (13th April 2021) - Benito, Xavier; Luethje, Melina; Schneider, Tobias; Fritz, Sherilyn C.; Baker, Paul A.; Pedersen, Eric J.; Gaüzère, Pierre; de Novaes Nascimento, Majoi; Bush, Mark; Ruhi, Albert
Abstract: Little is known about whether changes in lake ecosystem structure over the past 150 years are unprecedented when considering longer timescales. Similarly, research linking environmental stressors to lake ecological resilience has traditionally focused on a few sentinel sites, hindering the study of spatially synchronous changes across large areas. Here, we studied signatures of paleolimnological resilience by tracking change in diatom community composition over the last 2000 years in four Ecuadorian Andean lakes with contrasting ecoregions. We focused on climate and anthropogenic change, and the type of biological responses that these changes induced: gradual, elastic, or threshold. We combined multivariate ordination techniques with nonlinear time‐series methods (hierarchical generalized additive models) to characterize trajectories of community responses in each lake, and coherence in such trajectories across lakes. We hypothesized that remote, high‐elevation lakes would exhibit synchronous trends due to their shared climatic constraints, whereas lower elevation lakes would show less synchronous trends as a consequence of human density and land‐cover alteration. We found that gradual and elastic responses dominated. Threshold‐type responses, or regime shifts, were only detected in the less remote lake, after a long period of gradual and elastic changes. Unexpected synchrony was observed in diatom assemblages from geographically distant and human‐impacted lakes, whereas lakes under similar broad‐scale environmental factors (climate and ecoregion) showed asynchronous community trajectories over time. Our results reveal a complex ecological history and indicate that Andean lakes in Ecuador can gradually adapt and recover from a myriad of disturbances, exhibiting resilience over century to millennial timescales.